(untitled) (Papeles, 2010)
The genre of travel literature at the beginning of the 20th century in Colombia puts into question once again the regional debate that exists within the process of nation building, as evidenced through the imaginary. The imagined, generally containing stereotypes, has been constructed by certain regions and withstood time as established referents in the collective memory of Colombians. This article examines these presuppositions through the analysis of two travel books: Journey on Foot by Fernando González, and Four Years Aboard Myself by Eduardo Zalamea. Both works treat the remote geography and frontiers of the country during this period.